Limb bone histology of theropod dinosaurs from the Early Jurassic of South Africa. Issue 2 (31st August 2022) - Weiss, Bailey M.; Botha, Jennifer; Choiniere, Jonah N.
ABSTRACT: Theropod dinosaurs likely radiated in the wake of the End-Triassic Extinction, but the early history of their diversification remains obscure. The Elliot Formation (EF) and its lateral equivalents in southern Africa preserves abundant continental Late Triassic and Early Jurassic vertebrate fossils, representing an opportunity to study the early phases of theropod evolution. However, Elliot Formation theropod remains are scarce relative to other dinosaurian groups, and most of the South African record pertains to a single taxon, Megapnosaurus rhodesiensis . We present morphological and osteohistological data on two theropod distal tibiae from South Africa's upper EF. The two new tibiae are larger than any known specimens of M. rhodesiensis, and they show a fast-growing woven-parallel complex (WPC). One of the specimens bears a line of arrested growth, but neither shows outer circumferential lamellae. These observations suggest that both specimens are immature and distinguishable from M. rhodesiensis based on osteohistology. Comparative anatomical observations, including body mass comparisons, further support this distinction. We cannot rule out an identification for one of our tibiae as Dracovenator regenti, the only other valid EF theropod taxon known from body fossils. Our observations indicate that there is likely at least one additional, relatively large-bodied upper EF theropod species that remains unknown from adequate skeletal material.